Relationship between Morphological Awareness and Vocabulary Mastery - Adam Adam (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
The aim of this research was to find out whether there is significant correlation between students’ morphological awareness and their vocabulary mastery. The sample of this research was thirty two students of SMK Kemilau Bangsa Batam. The design of this research used ex-post-facto design in term of co-relational study. The instruments were Morphological Awareness and vocabulary tests. The result of calculation showed that coefficient correlation was higher than the critical value of r table (0.7290.449). Simple regression was done to analyze how far the contribution of morphological awareness to students’ vocabulary mastery. The result revealed that morphological awareness influenced 51.5% toward students’ vocabulary mastery. Therefore, it can be concluded that there is a significant correlation between students’ morphological awareness and their vocabulary mastery. It is implied that morphology can be applied as strategy of increasing students’ vocabulary mastery.